Review on Sustainability Management Using Zero Waste Concept for Building Construction (International Journal of Innovative Research in Computer Science & Technology, 2020)
All over the world, construction anddemolition (C&D) waste is generated in enormous amountwhich leads to various environmental problems. The wasteis dumped illegally or into the landfills which degrades thesoil and causes pollution. To eliminate the problem of C&Dwaste management, the concept of zero waste for buildingconstruction has been studied in this work. This study aimsat finding out the possible research gaps in the managementof construction and demolition waste and extant literaturesurvey was done on the sustainability management usingzero waste concept.
Keywords: Zero waste; Sustainability; C&D waste; Construction; Management